Strengthening/building national accreditation bodies - Ashton, Alvin A. (1999)
Seeks to identify the constraints to the implementation of the decisions relating to the strengthening/building/establishing national accreditation bodies in the Bahamas, Haiti and Belize, and to develop an Action Plan to address the constraints identified.